# Trigonometry

posted by .

prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1

• Trigonometry -

LS
= [(cscx - cotx)(cscx + cotx)]^4
= [csc^2x - cot^2x]^4
= [1 + cot^2x - cot^2x]^4
= [1]^4
= 1
= RS

## Similar Questions

1. ### calculus

express in sinx 1 1 ---------- + -------- cscx + cotx cscx - cotx and express in cosx 1 + cot x ------- - sin^2x cscx = 1/sinx so what do i do w. that extra one on the top!?
2. ### trig

express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
3. ### drwls

My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
4. ### Pre-Calculus

Find a numerical value of one trigonometric function of x if tanx/cotx - secx/cosx = 2/cscx a) cscx=1 b) sinx=-1/2 c)cscx=-1 d)sinx=1/2
5. ### Precalculus

Simplify:[(cscx-cotx)(cscx+cotx)]/cscx
6. ### Math

prove:(cscx-cotx)^4 x (cscx+cotx)^4 = 1
7. ### ap calc bc

hi! ok, i know that deriv(cscx) = -cscxcotx and that deriv(cos) = -sinx deriv(cotx) = -((cscx)^2) my question is: is this (statements below) correct?
8. ### Trig

prove (cscx-secx/cscx+secx)=(cotx-1/cotx+1)
9. ### trig

Prove (cscx+cotx)(cscx-cotx)=1
10. ### Math

Im really struggling with these proving identities problems can somebody please show me how to do these?

More Similar Questions